2021
DOI: 10.3390/nu13093286
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Protein Imbalance during Pregnancy on the Growth, Metabolism and Circulatory Metabolome of Neonatal and Weaned Juvenile Porcine Offspring

Abstract: Protein imbalance during pregnancy affects women in underdeveloped and developing countries and is associated with compromised offspring growth and an increased risk of metabolic diseases in later life. We studied in a porcine model the glucose and urea metabolism, and circulatory hormone and metabolite profile of offspring exposed during gestation, to maternal isoenergetic low–high (LP-HC), high–low (HP-LC) or adequate (AP) protein–carbohydrate ratio diets. At birth, LP-HC were lighter and the plasma acetylca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…ACSL6 converts long-chain fatty acids to acyl-CoAs ( 30 ). Previous studies showed that HP intake increased the concentration of lysine and methionine, which increased l -carnitine production in the liver in pigs ( 31 , 32 ). l -carnitine can transport acyl-CoA into the mitochondrial matrix to promote fatty acid β-oxidation, which can be biosynthesized by l -lysine and l -methionine as substrates in the body ( 33 ), suggesting that SPH infusion accelerates fatty acid β-oxidation in the liver.…”
Section: Discussionmentioning
confidence: 88%
“…ACSL6 converts long-chain fatty acids to acyl-CoAs ( 30 ). Previous studies showed that HP intake increased the concentration of lysine and methionine, which increased l -carnitine production in the liver in pigs ( 31 , 32 ). l -carnitine can transport acyl-CoA into the mitochondrial matrix to promote fatty acid β-oxidation, which can be biosynthesized by l -lysine and l -methionine as substrates in the body ( 33 ), suggesting that SPH infusion accelerates fatty acid β-oxidation in the liver.…”
Section: Discussionmentioning
confidence: 88%